2015
DOI: 10.1002/pssa.201431866
|View full text |Cite
|
Sign up to set email alerts
|

A study of structural and wear properties of PACVD deposited a‐C:H thin films for application as protective layers on Al alloys

Abstract: Due to the high strength-to-weight ratio, aluminum alloys are commonly used materials in aircraft and automotive industries. However, the low hardness and wear resistance and high friction coefficient limit their applications. In this study, we deposited a-C:H thin films on 7075 Al alloy substrates without an interlayer by direct current PACVD method. Negative substrate bias was varied to improve the surface mechanical properties. We obtained smooth, homogenous, and well adhered up to 28 mm thick a-C:H layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In this regard, surface coating can be a feasible option to improve the strength and hardness of these alloys. Extensive studies have been reported which highlight an improvement in hardness and wear performance of aluminium alloy by the application of various thermal spray techniques [22][23][24][25]. A remarkable improvement in surface hardness was achieved by the application of binary TiN/TiAl coatings and witnessed almost 10 times higher hardness than the uncoated AA5083 [26].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, surface coating can be a feasible option to improve the strength and hardness of these alloys. Extensive studies have been reported which highlight an improvement in hardness and wear performance of aluminium alloy by the application of various thermal spray techniques [22][23][24][25]. A remarkable improvement in surface hardness was achieved by the application of binary TiN/TiAl coatings and witnessed almost 10 times higher hardness than the uncoated AA5083 [26].…”
Section: Introductionmentioning
confidence: 99%
“…There are various deposition methods employed to produce DLC films, such as sputtering, [5][6][7] filtered-arc deposition, 8) pulsed laser ablation, 9) and plasma-enhanced chemical vapor deposition (PECVD). 10,11) Among these method, PECVD is widely used to prepare a-C:H films from hydrocarbon discharges owing to its advantages of considerably low deposition temperature, higher throughput, and uniform deposition area. 12,13) PECVD involves chemical processes that occur in the vapor phase on the substrate surface to form films.…”
Section: Introductionmentioning
confidence: 99%